IMPOVERISHMENT RISKS AND THE HUMAN COST OF INDIRA SAGAR DAM PROJECT: A CASE STUDY OF DEVARAGONDI VILLAGE IN ANDHRA PRADESH - Kumar, K. Anil; Chikkala, Nagaraju (International Journal of Allied Research in Sociology and Anthropology, 2023)
Development-induced displacement is a global phenomenon with severe implications for the socio-economic rights and livelihoods of affected communities. This study examines the specific impacts of the Indira Sagar multipurpose project on the village of Devaragondi in Andhra Pradesh, India, where over two lakh people, mainly tribal communities, were displaced. The study uses anthropological tools to assess impoverishment risks, including landlessness, joblessness, homelessness, marginalization, food insecurity, and loss of access to common property resources. The study reveals that inadequate implementation of the rehabilitation and resettlement policy has exacerbated impoverishment risks for the displaced people, including loss of their traditional livelihoods and displacement from their ancestral lands. The study underscores the need for effective policy implementation and adequate compensation and support for displaced communities to mitigate impoverishment risks associated with involuntary displacement. The study highlights the vulnerability of tribal communities to displacement due to concentration of development projects in their areas